Assessing the cultural relevance of INSIGHTS for Jamaica [PowerPoint presentation] - McClowry, Sandee; Spellmann, Mark (My University, 2013)
The purpose of this study was to assess the cultural resonance and dissonance of "INSIGHTS into Children's Temperament" as a first step in adapting the intervention for dissemination in Jamaica. INSIGHTS is an evidence-based intervention that enhances the development of school-age children and the child management skills of their teachers and parents. The intervention was developed with extensive input from stakeholders in high poverty neighborhoods in New York City. Thirty-two Jamaican educators attended a two-day INSIGHTS workshop. At the conclusion, the educators were asked to evaluate whether INSIGHTS resonates with the "deep structures" of Jamaican cultural values and beliefs. A thematic content analysis of their verbal and written comments supported that the deep structures of the intervention resonates well with Jamaican culture. The themes that emerged included: INSIGHTS gives Jamaican educators and parents new strategies to replace harsh discipline; offers new perspectives, providing more developmentally appropriate and sophisticated ways of seeing things; and provides practical strategies and solutions. Additional comments addressed "surface level" elements that would make the intervention more accessible and appealing for Jamaican audiences. Suggestions included remaking the intervention's videotapes at local schools and capturing the specific challenges faced by Jamaican teachers and children
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Intervention programmes; INSIGHTS into Children's Temperament; Programme evaluation; Child development; Skill development; Jamaican teachers; Teacher attitudes; Cultural factors; Conference papers; Jamaica